Perkembangan dan Tantangan Koperasi Syariah di Indonesia - Puspita Hermawan, Adi; Ardiyansyah, Fikky; Ariyanto Setiyo Wahyudi, Rudhi (Universitas Koperasi Indonesia, 2024)
Sharia cooperatives in Indonesia have become an important element in the sharia financial system which is based on Islamic values, such as justice, cooperation and equality. The development of sharia cooperatives in Indonesia can be traced to the early 1900s, with the establishment of Baitul Maal Wa Tamwiil (BMT) Insan Kamil in 1992 which marked an important moment in the history of sharia cooperatives in this country. This cooperative was formed to provide financial services in accordance with sharia, by avoiding usury, uncertainty (gharar), and speculation (maysir), which are contrary to Islamic teachings. According to data from the ODS of the Indonesian Ministry of Cooperatives and SMEs, the number of Sharia Savings and Loans Cooperatives (KSPS) increased from 3,905 units in 2019 to 4,011 units in 2023. This research examines the developments and challenges faced by sharia cooperatives in Indonesia. The aim of this research is to identify the opportunities and obstacles faced by sharia cooperatives in facing the development of the sharia financial industry in Indonesia. The research method uses descriptive analysis with secondary data from the Ministry of Cooperatives and SMEs as well as sharia financial indicators. The research results show that sharia cooperatives have challenges in terms of sharia financial literacy and limited capital. Apart from that, Sharia Cooperatives also have great opportunities with the support of a significant Muslim population and government regulations. The implications of this research are expected to help sharia cooperatives in increasing the competitiveness and sharia financial literacy of their members.